Pertahanan dan Keamanan Berlandaskan Prinsip Pancasila Bagi Generasi Produktif Menuju Indonesia Emas 2045 - Muhammad Arbani (Jurnal Syntax Admiration, 2025)
The vision of "Golden Indonesia 2045" targets Indonesia as a developed country based on Pancasila values to create solid national stability. The productive generation holds a strategic role as a pioneer in defending state sovereignty through strengthening the ideological values and character of the nation. This research identifies the application of Pancasila values in the defense and security sector as an important step to face global challenges, such as the threat of radicalism, disinformation, and cyberattacks. With a multidisciplinary approach involving education, government policies, technology, and community support, strengthening national resilience can be realized in a sustainable manner. This article also reviews the challenges of implementing Pancasila in the era of globalization and strategies to increase the role of the productive generation towards a Golden Indonesia 2045.